Relasi antara Agama dan Negara dalam Islam : Refleksi atas Ideal Agama dan Realitas Sejarah - Alfitri - (Millah: Journal of Religious Studies, 2003)
This article aims to provide an analysis about the relationship between religion and state in Islamic perspective, with critical observation on Islamic, ideal-moral of politics and its historical reality. For that, this article tries to discuss the Islamic precepts of politics in the Koranand Prophet traditions, let alone their practice in Islamic history. After that, an effort of political dialectics in Islam being mapped. Finally, they are reflected in order to sum a conclusions. Having discussed this theme, it is clearthat it is noteasy to reach a final and absolute conclusion about ideal relationship between Islam and state in the modern era. Whether Islam is being practiced as its formal form or substantive form, always become controversy since its origins. But the most important thing, to answer the question is Islamic response of political problem must describe universal-humane-long-term solutions, instead.